Functional Insights From the Evolutionary Diversification of Big Defensins - Gerdol, Marco; Schmitt, Paulina; Venier, Paola; Rocha, Gustavo; Rosa, Rafael Diego; Destoumieux-Garzón, Delphine (Frontiers in Immunology, 2020)
Big defensins are cationic antimicrobial polypeptides believed to be the ancestors of β-defensins, the most evolutionary conserved family of host defense peptides (HDPs) in vertebrates. Nevertheless, big defensins underwent several independent gene loss events during animal evolution, being only retained in a limited number of phylogenetically distantly invertebrates. Here, we explore the evolutionary history of this fascinating HDP family and investigate its patchy distribution in extant metazoans. We highlight the presence of big defensins in various classes of lophotrochozoans, as well as in a few arthropods and basal chordates (amphioxus), mostly adapted to life in marine environments. Bivalve mollusks often display an expanded repertoire of big defensin sequences, which appear to be the product of independent lineage-specific gene tandem duplications, followed by a rapid molecular diversification of newly acquired gene copies. This ongoing evolutionary process could underpin the simultaneous presence of canonical big defensins and β-defensin-like sequences in some species. The big defensin genes of mussels and oysters, two species target of in-depth studies, are subjected to gene presence/absence variation (PAV), i.e. they can be present or absent in the genomes of different individuals of the same species. Moreover, we observed that big defensins follow different patterns of gene expression within a given species and respond differently to microbial challenges, suggesting functional divergence. Consistently, current structural data show that big defensin sequence diversity affects the 3D structure and biophysical properties of these polypeptides. We discuss here the role of N-terminal hydrophobic domain, lost during evolution towards β-defensins, in the big defensin stability to high salt concentrations and its mechanism of action. Finally, we discuss the potential of big defensins as markers for animal health and for the nature-based design of novel therapeutics active at high salt concentrations.